Edukasi Literasi Perbankan Syariah kepada Anak Usia Dini di Taman Kanak-Kanak Tarbiyatul Athfal Gampong Blang Crum Kandang Kecamatan Muara Dua Lhokseumawe - Hidayatina, Hidayatina; Mardhiah, Ainun; Khairina, Khalish (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
In order to instill the virtue of frugal living, it is imperative to educate children on the practice of saving from an early age. Sharia-compliant banks offer a secure platform for savings. A recent educational initiative undertaken at Tarbiyatul Athfal Kindergarten, Lhokseumawe, on Thursday, July 11, 2024, using an interactive lecture approach to impart a comprehensive understanding of Sharia banking and its associated terms to young children. This program effectively equipped the children with a sound grasp of Sharia banking, as evidenced by their successful responses during the evaluation phase